THE EFFECT OF USE OF AUDIO VISUAL-BASED LITERACY LEARNING ON THE READING ABILITY OF CLASS III STUDENTS AT INPRES TANGKALA 1 PRIMARY SCHOOL, MAKASSAR CITY - Ashara Dewi Pertiwi Suparto; Badruddin Kaddas; Nur Syam (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Literacy abilities were originally defined as reading and writing skills, but nowadays their implementation is experiencing development, literacy abilities are an important ability that every student must have to master various subjects. This research aims, 1) To find out an overview of the implementation of audio-visual-based literacy learning; 2) Ulntulk to know how students' reading abilities are; 3) Knowing the influence of implementing audio-visual based literacy learning. This research is categorized as a type of prel-elkspelrimeln research. Research uses quantitative research because the data obtained by the research does not include numerical data. The research design used in this research is Onel-Groulp Prel telst-Posttelst Delsign. Based on the results of observations of students' activities while pursuing audio-visual-based literacy learning, the results of the research show that there is a significant influence on the development of audio-visual media on the reading ability of students in class III at SD INPRElS TANGKALA 1 MAKASSAR CITY on the results of international financial statistics by visiting Eat the ultimate rulmuls, then The calculation of thitulng < ttabell was obtained, namely 9.831 < 1.753 and a significance value of 0.00 < 0.05. So Ho is rejected and Ha is accepted. In this way, the development of visual audio media has had an impact on reading ability.